Maritime Innovation and Restructuring Of The Nusantara Shipping Network In The Traffic Of History - Muhammad Rafi Rabbani; Leli Yulifar (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2026)
This article examines the role of maritime innovation in driving the restructuring of the Nusantara shipping network throughout history, from the Hindu-Buddhist period, the Islamic period, to the early arrival of Westerners. The sea was positioned as a strategic historical space, not only as a means of mobility and trade, but also as a medium for cultural exchange, technology, and power. This research uses a literature study method with a historical approach to trace the development of shipping networks chronologically and analyze their relationship to social, economic, and political dynamics. The results of the study indicate that maritime innovation, including developments in ship technology, navigation systems, port management, and shipping organizations, was a key factor in changing the structure of the Nusantara shipping network. Maritime kingdoms such as Srivijaya, Majapahit, and Islamic sultanates built their political power and legitimacy through control of strategic sea lanes and ports, reflecting the character of thalassocratic power. During the Islamic period, shipping networks strengthened and played a significant role in the intensification of inter-island trade, the formation of cosmopolitan port cities, and the spread of Islam through peaceful mechanisms. However, the restructuring of shipping networks also had complex implications in the form of interregional inequality and changing power relations, particularly after the arrival of Western nations. This study emphasizes that maritime innovation cannot be understood solely as technical progress, but rather as a historical process that reshaped the economic, social, and political order of the Nusantara maritime world.